PERANAN KUD SEMBADA PUSPO SEBAGAIPENGGERAK PEMBANGUNAN EKONOMI DESA DITINJAU DARI PERSPEKTIF EKONOMI ISLAM (DI KECAMATAN PUSPO KABUPATEN PASURUAN ) - Aqidah, Waqi’atul (Finance : Journal of Accounting and Finance, 2023)
This study aims to examine the role of Koperasi Unit Desa (KUD) Sembada Puspo as a driver of village economic development in Puspo Sub-district, Pasuruan Regency, from the perspective of Islamic economics. This research employs a qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that KUD Sembada Puspo plays a significant role in supporting the village community's economic activities through the provision of business capital, job creation, and support for small and medium enterprises. From an Islamic economic perspective, this role aligns with the principles of Sharia, such as justice, mutual cooperation (ta‘āwun), and the avoidance of riba (usury). The cooperative also applies transparency and accountability in fund management and contributes to the collective welfare (maslahah ‘āmmah). Thus, KUD Sembada Puspo serves not only as an economic institution but also as a means of empowering rural communities based on Islamic values.